Critical Review of Interdisciplinary Approaches to Mental Health and Well-Being - Alsubaie, Abdullah Fahad Musaed; Almutairi, Raed Maniaullah Ateeqaullah; Alraseni, Waleed Saleh Hamad; ALmutairi, Abdullah Safar; Al-Mansour, Abdulaziz Ahmed Abdulaziz; Hazzazi, Thamer Ahmed Ail; Alfarsy, Ali Abdu; Alanazi, Ghazi Khalaf; Alotaibi, Khalid Fahad; Alshardan, Abdullah Ibrahim (Journal of Ecohumanism, 2024)
Mental health and well-being should be the goal of the healthcare system to provide all possible, available, and sustainable quality care to clients; in exchange, faced with a myriad of similar threats experienced by healthcare systems across the world, it suffers from the failure to provide healthcare by compromising on the three; accessibility, quality, and equity. Thus, the present work brings an overview of the key areas in global health systems with a focus on demands’ differences, pandemics’ impact, resource distribution, and policy/health system issues. In this paper, the literature will be reviewed and analyzed, and recommendations will be made to address the identified problems. Analyzing these global issues, the study aims to enhance understanding of issues in existing healthcare practices, government policies, and technological advancements to create a better future by offering ways of delivering needs effectively.